Solución Numérica de Ecuación de Burgers - Luna Valdez, Juan (2016)
In this paper the problem of Burgers is studied in the simplest case, some results of existence, uniqueness and regularity of the solution of the problem are indicated, and in its variational form it is given a result that gives a suÿcient condition for a function to be weak solution. But as the solution may present discontinuities, then we pass on to a new equation by adding a term of artificial viscosity, thus obtaining a viscous solution for equation whose results converge to the solution of the Burgers equation when the viscous term tends to zero. Therefore we study the viscous equation from a numerical point of view.